An Analysis of Interlingual and Intralingual Errors in EFL Learners’ Composition - Rahmila Murtiana (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
This study aims to investigate the occurrence of errors committed by EFL learners in their composition in terms of interlingual and intralingual errors. The setting of the study was a state Islamic university in Banjarmasin South Kalimantan, Indonesia. The research participants were undergraduate students majoring in English Education. Data were collected through documentation of students’ composition and analyzed based on Corder’s Error Analysis (EA) theory. From the samples of 38 compositions submitted, it was identified that interlingual errors occurred more frequently than intralingual errors. Interlingual errors comprised morphological selection, lexical selection, syntactical selection, and misordering. Meanwhile, intralingual errors were evident in both omission and addition in the areas of word formation and syntax. The findings of this study revealed that first language interference caused more errors in writing than learners’ incomplete process of acquiring second language rules. To prevent the errors from being fossilized, it is suggested that in the teaching and learning process, language instructors provide continuous corrective feedback, and learners be more active in finding exposure to the correct form of the target language.AbstrakPenelitian ini bertujuan untuk menyelidiki terjadinya kesalahan yang dilakukan oleh pembelajar bahasa asing dalam tulisan mereka yang berupa kesalahan interlingual dan intralingual. Penelitian dilakukan di sebuah universitas Islam negeri di Banjarmasin Kalimantan Selatan Indonesia. Partisipan penelitian adalah mahasiswa S1 jurusan Pendidikan Bahasa Inggris. Data diperoleh melalui dokumentasi hasil karangan mahasiswa yang kemudian dianalisa berdasarkan teori Error Analysis dari Corder. Sebanyak 38 sampel karangan mahasiswa dikumpulkan dan ditemukan bahwa kesalahan interlingual lebih banyak terjadi daripada kesalahan intralingual. Kesalahan interlingual berupa kesalahan dalam memilih kosa kata dan menyusun kalimat yang disebabkan oleh pengaruh bahasa asli. Sedangkan kesalahan intralingual berupa penghilangan atau penambahan yang tidak tepat pada bentuk kata atau bentuk kalimat. Hasil penelitian menunjukkan bahwa pengaruh bahasa asli yang menyebabkan kesalahan interlingual dalam tulisan terjadi lebih banyak daripada kesalahan intralingual. Untuk mencegah melekatnya kesalahan, disarankan agar dalam proses belajar mengajar guru dapat terus memberikan umpan balik, dan siswa harus lebih aktif dalam mencari contoh-contoh bentuk bahasa yang benar.Kata Kunci: kesalahan, interlingual, intralingual, karangan